KAJIAN PEMANFAATAN PEMBENAH TANAH UNTUK PERTANIAN BERKELANJUTAN PADA LAHAN SAWAH SUB OPTIMAL DI PROPINSI LAMPUNG - Ishak Juarsah; Rakhmiati Rahmiati; Etik Puji Handayani; Yatmin Yatmin (Jurnal WACANA PERTANIAN, 2018)
The study was conducted in Central and East Lampung District with consideration for soil fertility in rice fields are planted with rice tends to go down, so that the harvest of dry grain production leveling off. The method used is a survey method, including primary data collection through interviews using questionnaires. Identification of using soil conditioner collected to reveal information about the type of soil conditioner that is known farmers and types soil conditioner once used by farmers. The aim of this study were: (1) an inventory of the type soil conditioner known and used by farmers, as well as the resources and applications dose; (2) determine the benefits and constraints use soil conditioner at the farm level, (3) to know fertilizer efficiency at the farmer level as the impact of soil conditioner utilizing, (4) to study soils conditioner prospect to increase land productivity. The results showed that the organic matter, soil conditioner types known and used in Central Lampung District is Zeolite Agro 2000, ZP.30 (enrichment zeolit with P nutrient) and dolomite, whereas in the East Lampung District is a regular zeolite and dolomite. The use of soil conditioner in both districts useful addition to increasing the production of rice crop about 10-30%, also improve soil fertility and increase the efficiency of nutrient uptake of inorganic fertilizers.